Essentials of Understanding Psychology - Feldman R. S. (New York St. Louis San Francisco Auckland McGraw-Hill, Inc., 1994)
Your students are individuals. Do your teaching materials treat them that way? Feldman's Essentials of Understanding Psychology does. Using a revolutionary revision process, Bob Feldman's Essentials of Understanding Psychology is a fully integrated learning system that gives students an even greater opportunity to achieve success, and brings the Students First goal to a new level. With an adaptive learning system that provides an individualized learning environment and helps students identify what they know, and more importantly, what they don't, every student has a unique experience refined to their needs.
Keywords: 159.9